Rigid‑body analysis of a beveled shape structure in regular waves using the weakly compressible smoothed particle hydrodynamics (WCSPH) method - Hikmatullah Sahib, Siti Ayishah Thaminah; Ramli, Muhammad Zahir; Azman, Muhammad Afq; Abd Rahman, Muhammad Mazmirul; Miskon, Mohd Fuad; Ariffin, Effi Helmy; Jeofry, Muhammad Hafeez; Yunus, Kamaruzzaman (Springer Nature, 2021)
In many cases of wave structure interactions, three-dimensional models are used to demonstrate real-life complex environments in large domain scales. In the seakeeping context, predicting the motion responses in the interaction of a long body resembling a ship structure with regular waves is crucial and can be challenging. In this work, regular waves interacting with a rigid foating structure were simulated using the open-source code based on the weakly compressible smoothed particle hydrodynamics (WCSPH) method, and optimal parameters were suggested for diferent wave environments. Vertical displacements were computed, and their response amplitude operators (RAOs) were found to be in good agreement with experimental, numerical, and analytical results. Discrepancies of numerical and experimental RAOs tended to increase at low wave frequencies, particularly at amidships and near the bow. In addition, the instantaneous wave contours of the surrounding model were examined to reveal the efects of localized waves along the structure and wave dissipation. The results indicated that the motion response from the WCSPH responds well at the highest frequency range (ω>5.235 rad/s).